A mixed-method taxonomy of child poverty: a case study from rural Ethiopia - Roelen, K; Camfield, L (Young Lives, 2012)
There are long-standing debates about how to measure poverty and well-being and how to classify household and individuals in terms of poverty status. This paper informs those debates. It presents a taxonomy of poverty and vulnerability that has been developed from a mixed methods study of rural children and households in Ethiopia. Qualitative information is used to inform and development of quantitative indicators that will assess poverty and vulnerability. The taxonomy was developed using a ’generic construction process’ that includes five steps: identification of the purposes of the study, formulation of a conceptual framework, selection and formulation of both the domains and then the indicators, and finally, construction of outcome measures. The data used in this construction process were gathered from children and adults across eight rural sites in Ethiopia. Children discussed their attitudes and views about what it meant to be poor. Additionally, adult responses were gathered about certain households. They were asked to classify specified households at present, and to recall how the same households were classified 25 years ago. This, along with household histories, provided a descriptive picture of change over time. Indicators that emerged included things like owning draught animals, which was a clear sign that a household was moving out of poverty. In contrast, owning no land or livestock indicated severe poverty. These indicators, identified through qualitative measures, form the basis for quantitative measures of poverty that are relevant to rural Ethiopian contexts. By constructing a taxonomy in this way, this study makes a significant contribution to the debates about how to measure poverty and classify individuals or households.